Subphrenic Abcesses and Their Thoracic Evolution - Saad, Eduardo N; Apestegui, Carlos; Luciani, Wilfrido; Suhl, Arnoldo (Cirugía del Uruguay, 1979)
This paper deais with thoracic complications and etiology related to evolution of subphrenic abcesses , in 2 series covering a 6 year period and 18 patients ( 11 men and 7 women) averaging an age o'f 50. In 15 (84 %) initial site was C.S.M .C. and in 3 (16 %) it was C.I.M .C. Different treatments resulted in favourable evolution in 13 cases ( 72 % ) .